Father's Day - Alden, Laura, 1955-; Hohag, Linda (Chicago : Childrens Press, 1994)
Sara and Steve plan an indoor fishing trip to surprise their father on Father's Day. Includes instructions for activities, songs, and fingerplays.
2.3
K-3
Keywords: Father's Day -- Juvenile fiction; Father's Day -- Fiction; Father's Day -- Fiction